1995
DOI: 10.1111/j.1365-2958.1995.18050859.x
|View full text |Cite
|
Sign up to set email alerts
|

yst gene expression in Yersinia enterocolitica is positively regulated by a chromosomal region that is highly homologous to Escherichia coli host factor 1 gene (hfq)

Abstract: Yersinia enterocolitica produces heat-stable enterotoxin (Y-ST) as one of its virulence factors. The yst gene, however, frequently and spontaneously becomes inactive (silent) during storage, which is accompanied by concurrent changes in some biological properties such as colony morphology, growth rate, carbon fermentation and ornithine decarboxylase activity. Northern blot analysis revealed that the level of mRNA for yst was repressed. To investigate the regulatory region, we transformed a yst-silent strain wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 15 publications
3
48
1
Order By: Relevance
“…For example, the oxyS gene transcript may inhibit rpoS translation by binding HF-1 and sequestering this molecule from rpoS leader RNA (Zhang et al, 1998). The H-NS histone-like protein has also been reported to antagonize rpoS mRNA translation (Yamashino et al, 1995).Regulation in Yersinia: an Update 155 and ElliottRecent studies conducted in Y. enterocolitica are consistent with this model: Yrp, the recently characterized HF-1 (Hfq) counterpart in Yersinia (also referred to as Ymr in certain databases) has been shown to control yst expression at the transcriptional level (Nakao et al, 1995). In line with these results, it was hypothesized that Yrp may exert its effect though the control of DNA topology (Nakao et al, 1995).…”
supporting
confidence: 62%
“…For example, the oxyS gene transcript may inhibit rpoS translation by binding HF-1 and sequestering this molecule from rpoS leader RNA (Zhang et al, 1998). The H-NS histone-like protein has also been reported to antagonize rpoS mRNA translation (Yamashino et al, 1995).Regulation in Yersinia: an Update 155 and ElliottRecent studies conducted in Y. enterocolitica are consistent with this model: Yrp, the recently characterized HF-1 (Hfq) counterpart in Yersinia (also referred to as Ymr in certain databases) has been shown to control yst expression at the transcriptional level (Nakao et al, 1995). In line with these results, it was hypothesized that Yrp may exert its effect though the control of DNA topology (Nakao et al, 1995).…”
supporting
confidence: 62%
“…As shown in Fig. 1, Hfq Pa shows considerable amino acid similarity to previously identified Hfq homologues from other Gram-negative bacteria (73 to 96 %) (Brown & Elliott, 1996 ;Chuang et al, 1999 ;Deckert et al, 1998 ;Durand et al, 1997 ;Fleischmann et al, 1995 ;Kajitani & Ishihama, 1991 ;Kaminski et al, 1994 ;Nakao et al, 1995 ;Robertson & Roop, 1999), whereas lower amino acid similarity (41 to 45 %) was found with putative Hfq homologues from three Grampositive bacteria. The multiple alignment (Fig.…”
Section: Sequence Similarity Between Hfq Pa and (Putative) Hfq Homolomentioning
confidence: 88%
“…Taken together with the above-described effects on specific genes, these results suggested that Hfq acts as a global regulator involved in the regulation of RpoS-dependent and RpoS-independent genes. Moreover, Hfq homologues have been reported to stimulate synthesis of the heat-stable enterotoxin in Yersinia enterocolitica (Nakao et al, 1995) and of the NifA protein in Azorhizobium caulinodans (Kaminski et al, 1994). Also, the Hfq homologue of Brucella abortus appears to be a major determinant of virulence in mice (Robertson & Roop, 1999).…”
Section: Abbreviationsmentioning
confidence: 99%
“…We were unable to observe CbpD in any mutants suggesting that (i) the reduction in cbpD transcription results in levels of CbpD that are too low to be detected by fluorescence staining of 2-DE separated proteins and/or (ii) the secretion system required to export CbpD also requires both QS systems. All mutants were deficient in the expression of PA4944, a protein with significant sequence similarity to host factor I (HF-I), an RNA-binding protein that regulates enterotoxin production in Yersinia enterocolitica (Nakao et al, 1995) and several virulence factors in Brucella abortus (Robertson & Loop, 1999). Previous reports have suggested that genes under the control of QS may also be regulated by other factors, including the alternative sigma factors RpoS (Van Delden & Iglewski, 1998) and PvdS (Ochsner et al, 1996).…”
Section: Discussionmentioning
confidence: 99%